Integration of Islamic Religious Education in the Development of Reading and Numerical Literacy Tests: An Analysis of the Rasch Model - Muhammad Reza; Fakhruddin Fakhruddin; Wiwi Isnaeni (Dinasti International Journal of Education Management And Social Science, 2025)
This article is in the form of the development of reading and numerical literacy tests that are integrated with Islamic religious education based on the lack of literacy skills test instruments that contain the context of Islamic religious education. The purpose of developing the test is to be able to measure literacy, numerical skills, and religious understanding as well as holistic values in the contextual realm. The object of the study was 109 students in 2 schools in Langsa Baro District. The research method is in the form of development (R&D) of the ADDIE model which includes Analysis, Design, Development, Implementation and Evaluation. Content validation showed material suitability (0.80), construction 0.0 and language clarity (0.82) with a point estimate rater of 0.799 (good) funds of 72% readability level good. Construct validation shows a minimum unidimensional of 28.3% variance and ideal instrument (p15%) and content validation for fit problems with the rasch model. The feasibility of the cronbach alpha reliability instrument is 0.96.obtained 80 items that are categorized as valid with the criteria of MNSQ, ZSTD and Pt Mean Corr and meet high reliability requirements, so that they can be used for formative or summative tests. This instrument is only limited to zakat, akiqah and qurbani materials as well as buying and selling. Therefore, it is necessary to continue to develop PAI materials and expand the number of respondents so that they can become a complete reference basis.